Neuroleptics Affect Kisspeptin mRNA Expression in the Male Rat Hypothalamus and Hippocampus - Pałasz, Artur; Rojczyk, Ewa; Suszka-Świtek, Aleksandra; Wiaderkiewicz, Ryszard (Pharmacopsychiatry, 2017)
Introduction: Kisspeptin has a multidirectional neuroendocrinal activity. It is especially considered to be a central regulator of reproductive function. Numerous data proved that neuroleptic administration may affect the peptidergic signaling in the various brain structures. However, there is no information concerning the relationship between treatment with neuroleptics and brain kisspeptin mRNA expression.Methods: We assessed the kisspeptin mRNA level in the hypothalamus and hippocampus of rats shortly and chronically (28 days) treated with haloperidol, chlorpromazine, and olanzapine using a quantitative Real-Time PCR method.Results: We have shown that all studied neuroleptics injected chronically have the ability to downregulate the kisspeptin mRNA expression in the hypothalamus, which may suggest the presence of an alternative mechanism for their orexigenic side effects. Long-term treatment with chlorpromazine increased the level of kisspeptin mRNA expression in the hippocampus.Discussion: Our results shed a new light on the pharmacology of antipsychotics and may contribute to a better understanding of alternative mechanisms responsible for their action. The study also highlights a complex nature of potential connections between dopamine transmission and brain kisspeptin pathways.
Keywords: kisspeptin; neuroleptics; hypothalamus; hippocampus